Ultrasonic-assisted synthesis of Nd-doped ZnO for photocatalysis - Oranuch Yayapao (2018)
Undoped and Nd-doped wurtzite hexagonal ZnO nanoneedles were successfully synthesized by ultrasonic-assisted solution method, and characterized by X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The photocatalytic efficiencies of the 0, 0.5 and 1% Nd-doped ZnO nanoneedles were evaluated by the degradation of methylene blue under UV light. In this research, the 1% Nd-doped ZnO is the best photocatalytic performance with 2.5 times of the undoped ZnO. © 2012 Elsevier B.V.